Impactos distributivos do financiamento dos regimes previdenciários no Brasil - Sergei Soares; Carolina Bloch (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper seeks to estimate the distributive impact of the taxes and other fiscal contributions that finance social security in Brazil. Making a certain number of strong hypotheses relative to the fiscal incidence of social security financing, we compute a measure of incidence that aggregates the distributive effect of the different taxes that compose tax revenues. For this, we use concentration coefficients computed by Silveira and Passos (2017) weighted by the importance of each tax in funding social security (basically by distinguishing individual social security contributions from taxes collected by the states and the Union). Our results indicate that the financing of social security in Brazil is only slightly progressive, given that the concentration coefficient of these taxes is not much lower than the Gini coefficient nor than the concentration coefficient of social security benefits.
Keywords: H22; H55; 330; fiscal incidence; social security